Factors associated with female genital mutilation in Burkina Faso and its policy implications - Karmaker, B.; Kandala, N.; Chung, Donna; Clarke, A. (BioMed Central Ltd., 2011)
Background: Female genital mutilation (FGM) usually undertaken between the ages of 1-9 years and is widely practised in some part of Africa and by migrants from African countries in other parts of the world. Laws prohibit FGM in almost every country. FGM can cause immediate complications (pain, bleeding and infection) and delayed complications (sexual, obstetric, psychological problems). Several factors have been associated with an increased likelihood of FGM. In Burkina Faso, the prevalence of FGM appears to have increased in recent years. Methods: We investigated social, demographic and economic factors associated with FGM in Burkina Faso using the 2003 Demographic Health Survey (DHS). The DHS is a nationally representative cross-sectional survey (multistage stratified random sampling of households) of women of reproductive age (15-49 years). Associations between potential risk factors and the prevalence of FGM were explored using χ2 and t-tests and Mann Whitney U-test as appropriate. Logistic regression modelling was used to investigate social, demographic and economic risk factors associated with FGM. Main outcome measures: i) whether a woman herself had had FGM; ii) whether she had one or more daughters with FGM. Results: Data were available on 12,049 women. Response rates by region were at least 90%. Women interviewed were representative of the underlying populations of the different regions of Burkina Faso. Seventy seven percent (9267) of the women interviewed had had FGM. 7336 women had a daughter of whom 2216 (30.2%) had a daughter with FGM and 334 (4.5%) said that they intended that their daughter should have it. Univariate analysis showed that age, religion, wealth, ethnicity, literacy, years of education, household affluence, region and who had responsibility for health care decisions in the household had (RHCD) were all significantly related to the two outcomes (p < 0.01). Multivariate analysis stratified by religion mainly confirmed these findings, however, education is significantly associated with a reduced likelihood of FGM only for Christian women. Conclusions and Policy implications: Factors associated with FGM are varied and complex. Younger women and those from specific groups and religions are less likely to have had FGM. A higher level of education may be protective for women from certain religions. Policies should capitalize on these findings and religious leaders should be involved in continuing programmes of action.